THE RISE OF DIGITAL MARKETPLACES AND THEIR ROLE IN SMALL BUSINESS GLOBALIZATION (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The rapid evolution of digital marketplaces has significantly reshaped the global business landscape, providing small enterprises with unprecedented access to international markets. These platforms eliminate traditional barriers such as geographical limitations, high operational costs, and complex supply chains, allowing small businesses to compete on a global scale. Through integrated payment systems, streamlined logistics, and data-driven insights, digital marketplaces enhance operational efficiency and customer engagement. Additionally, they foster innovation by enabling businesses to adapt quickly to changing consumer demands. However, despite these advantages, challenges remain. Issues such as platform dependency, regulatory constraints, data security risks, and market saturation pose potential threats to small business sustainability. Furthermore, increased competition from both local and international players forces businesses to adopt strategic approaches for long-term success. This paper examines the transformative role of digital marketplaces in small business globalization, analyzing both the opportunities and challenges they present in an increasingly interconnected digital economy.
Keywords: Digital marketplaces; small business globalization; e-commerce platforms; global trade; online entrepreneurship; cross-border commerce; digital economy